Website Based E-Module Development on Computer System in Vocational High School - Nesia Yolanda; Fahmi Rizal (Universitas Negeri Padang, 2021)
The problem in this research is that in computer system learning, there is no special media for online learning. During the learning process using teaching materials in the form of power points. The teacher as a facilitator must be able to provide facilities that support teaching and learning, this is not in accordance with existing conditions in the field, the teacher does use information and communication technology-based media, but the use of power point media is still not optimal, there is no video, simulation and evaluation . In addition, during this pandemic situation, the learning process is less effective, because the face-to-face learning process is divided into 2 shifts. In this condition, online-based learning media is demanded. This has an impact on the grade X computer value system of TKJ majors at SMKN 1 Painan. The method used in this research is research and development (R&D). The development model used is the 4-D model development. The 4-D development model consists of 4 stages, namely Definition, Design, Development and Deployment. The results showed that: (1) this research has produced a website-based learning module product for computer system subjects at SMK Negeri 1 Painan using a domain, namely https://emodulsiskom.com/smkn1painan/ which can be accessed by teachers and students. with a computer, laptop, or smart phone connected to the internet via a web browser whenever and wherever they are. (2) The E-Module on the subject of Computer Systems that was developed is valid, practical and effective.